News in antimicrobial therapy. Part II – Gram-positive cocci - Drzewiecki, Artur; Bulanda, Małgorzata (Przewodnik Lekarza/Guide for GPs, 2005)
In this part we have described news in antimicrobial therapy concerning Gram-positive cocci.